(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2022)
Thanks to the introduction of modern management strategies in the world, the scale of the effective integrationof industry into innovative development of the industry has been expanding. Therefore, the article outlines theimplementation of modern innovative management strategies, improvements in agricultural production, particularly inthe production and processing of horticultural products, the supply of raw materials for the industry, their integration,and the impact of factors affecting the production process